Osmosis dehydration of sweet corn (Zea mays saccharata.) kernel with trehalose solution. Issue 1 (November 2021) - Susilo, B; Lutfi, M; Lu'ay, H E
Abstract: Osmosis dehydration is a process of reducing water content by immersing the material in a hypertonic solution. It usually uses a sugar solution likes mono-saccharide or disaccharide. Trehalose is one type of disaccharide that can be used as a solute. Trehalose is able to maintain the nutrition content of food material and the aroma of horticulture products because it maintains and stabilizes complex molecules. Immersing of sweet corn kernel in trehalose solution was expected to maintain kernel sweet corn quality in relation to the next process. The objective of the research is to investigate the effects of the different immersing temperatures and trehalose concentrations on the physical quality of sweet corn. This study used solution with concentrations of 4%, 8%, and 12% trehalose. The variations of immersing temperature were 30°C, 40°C, and 50°C. The experiment was done with a factorial completely randomized design. The first factor was immersing temperature and the second factor was the concentration of trehalose solution. The data was analyzed using Duncan Multiple Range Test (DMRT) method. The temperature treatment of 50°C and trehalose concentration of 12% showed the highest weight reduction (6.18%), solid gain (4.5%), and water loss (10.38%). The lowest water content of corn kernel was also obtained in this treatment i.e 78.7%.